Production and characterization of Pectic enzymes from three fungi - M. Abdel-Rahim, Awad; A. Elmustafa, Amina (Gezira Journal of Engineering and Applied Sciences; مجلد 8 عدد 2 (2013), 2013)
Pectins are compounds  that  are resistant   to  enzymatic  cleavage  in most  organisms  and  plants, Studies  were  therefore  made towards finding methods for hydrolyzing these compounds. One such approach  is enzymatic hydrolysis.  Three fungi   (Trichoderma   viride,    Asperigillus     niger   and penicillum   digitatum)  are   used   for  production   of   pectinase  enzymes, Two  methods (reducing  sugar and viscometary)  were  used  for  measuring enzymes activities. Pectin and sodium polypectate compounds were used  as substrates. The  production of  pectinases by the three fungi was investigated in culture media. T. viride and P. digitatum  gave  maximum   production  of pectinase  enzymes  after  two  week  and  A. niger  gave  it  after  one week. Purification   by   ammonium    sulphate   precipitation,     showed   that   the maximum  pectinase  activity  was  at   80%   concentration for both fungi A niger and P. digitatum. By using  gel  electrophoresis, five bands were found to   give   pectinase  enzymes   activities. The   present   study   showed    the importance   of   fungi   as   sources  of  enzymes and recommends that more studies  must   be   done   in   the  field of  biotechnology to produce glucose  from natural products by  using fungi.